The Moderating Effects Of Business Environment On The Relationship Between Foreign Direct Investment And Economic Growth In China - Wang, Jiechen (2024)
Over the last 30 years, china has experienced outstanding economic growth and has emerged as a key destination for substantial foreign direct investment (fdi). However, the pace of fdi inflows has decelerated in recent years. In response, the chinese government has introduced a policy to enhance the business environment. Motivated by this economic scenario, this study focuses on the role of fdi inflows and the business environment in promoting china’s economic growth from 1985 to 2020. This study constructs business-environment indicators concerning institutional quality, financial development, infrastructure, and innovation using the entropy weight method. Subsequently, this study employed econometric techniques such as unit root tests and johansen-juselius cointegration tests to determine the order of integration of the variables and the presence of long-run relationships. This study not only focuses on the direct relationship but also profoundly explores the impact of fdi on china's economic growth by considering the role of the business environment as a moderating factor. Furthermore, each sub-element of the business environment is explored separately to understand their respective impacts better. This study confirms that fdi and economic growth in china have a long-run relationship.